2015
DOI: 10.1371/journal.pgen.1005357
|View full text |Cite
|
Sign up to set email alerts
|

FUS Interacts with HSP60 to Promote Mitochondrial Damage

Abstract: FUS-proteinopathies, a group of heterogeneous disorders including ALS-FUS and FTLD-FUS, are characterized by the formation of inclusion bodies containing the nuclear protein FUS in the affected patients. However, the underlying molecular and cellular defects remain unclear. Here we provide evidence for mitochondrial localization of FUS and its induction of mitochondrial damage. Remarkably, FTLD-FUS brain samples show increased FUS expression and mitochondrial defects. Biochemical and genetic data demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
171
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(190 citation statements)
references
References 100 publications
19
171
0
Order By: Relevance
“…Our recent work has shown that fused in sarcoma/translocated in liposarcoma (FUS/TLS or FUS), a nuclear RNA binding protein, interacts with and targets mitochondria (Deng et al, 2015). This prompted us to carefully examine effects of wild-type and ALS-mutant FUS on axonal mitochondrial transport.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent work has shown that fused in sarcoma/translocated in liposarcoma (FUS/TLS or FUS), a nuclear RNA binding protein, interacts with and targets mitochondria (Deng et al, 2015). This prompted us to carefully examine effects of wild-type and ALS-mutant FUS on axonal mitochondrial transport.…”
Section: Resultsmentioning
confidence: 99%
“…To further examine FUS activity in vivo , we used our previously established fly model for FUS proteinopathy (Chen et al, 2011; Deng et al, 2015). We crossed mitoGFP into the transgenic flies expressing human Wt- or P525L-mutant FUS to track mitochondrial movement in motor neuron axons of these transgenic flies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, other chaperones such as HSP70/Hsc70, cyclophilin-A, aB-crystallin and glutathione peroxidase have no effect in blocking SOD1 misplacing onto the mitochondrial outer membrane which consequently, leads to damaged mitochondrial integrity [176]. Recently, reduced expression of HSP60 has exhibited the protective role against mitochondrial damage in ALS because interaction between mitochondrial chaperonin, HSP60 and FUS protein causes its translocation to mitochondria and leads to cell damage [177]. Further, it has been reported that small HSPs, including the HSP27, HSP25 and α-crystallin family also impart neuroprotective and cardioprotective effect against secondary complications of T2D [178].…”
Section: Chaperones Mediated Therapy For Altered Mitochondrial Dynamicsmentioning
confidence: 99%
“…And RNA binding proteins could be potential targets in prostate cancer [13]. RNA binding protein FUS has been shown to interact with HSP60 (Heat Shock Protein Family 60) to promote mitochondrial damage [14]. FUS-CHOP promotes invasion in myxoid liposarcoma through a SRC (SRC Proto-Oncogene, Non-Receptor Tyrosine Kinase)/FAK (Focal Adhesion Kinase)/RHO (Rhodopsin)/ROCK (Rho Associated Coiled-Coil Containing Protein Kinase)-dependent pathway [15].…”
Section: Introductionmentioning
confidence: 99%